2005
DOI: 10.1515/bc.2005.011
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of insulin-like growth factor binding proteins (IGFBPs) by calpain

Abstract: Calpains are non-lysosomal, Ca 2q -dependent cysteine proteases, which are ubiquitously distributed across cell types and vertebrate species. The rules that govern calpain specificity have not yet been determined. To elucidate the cleavage pattern of calpains, we carried out calpain-induced proteolytic studies on the insulin-like growth factor binding proteins IGFBP-4 and -5. Proteolysis of IGFBPs is well characterized in numerous reports. Our results show that calpain cleavage sites are in the non-conserved u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…PDGF is known to exert a survival effect on O-2A progenitors in vitro (Barres et al 1992). The potential role of extracellular proteolytic activity on growth factors and/or their receptors cannot be excluded, as has been shown for insulin-like growth factors (Ghosh et al 2005). The cell stage-dependent effects reflect previously observed maturation-dependent sensitivity of oligodendrocytes to hypoxia and other insults (Back et al 2007).…”
Section: Role Of Pdgf and Cell Maturitymentioning
confidence: 85%
See 1 more Smart Citation
“…PDGF is known to exert a survival effect on O-2A progenitors in vitro (Barres et al 1992). The potential role of extracellular proteolytic activity on growth factors and/or their receptors cannot be excluded, as has been shown for insulin-like growth factors (Ghosh et al 2005). The cell stage-dependent effects reflect previously observed maturation-dependent sensitivity of oligodendrocytes to hypoxia and other insults (Back et al 2007).…”
Section: Role Of Pdgf and Cell Maturitymentioning
confidence: 85%
“…1992). The potential role of extracellular proteolytic activity on growth factors and/or their receptors cannot be excluded, as has been shown for insulin‐like growth factors (Ghosh et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The extreme sensitivity of natively disordered regions to proteolytic cleavage might be attributed to their surface accessibility and flexibility. Several studies on the structural requirements of proteolysis also show that proteolytic cleavage predominantly occurs at unstructured regions 11–14, 46. Secondary structure analysis of the 106 calpain substrates showed that the enzyme predominantly cleaves in the disordered regions 13.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments by Tompa and Friedrich (2000) and Li et al (2004) have shown that calpain autolyses within the first 30 min, which results in protease activation. Our previous studies on calpain action on IGFBPs (insulin-like growth factor binding proteins) showed the same cleavage pattern, for 1, 2 and even 4 h (Ghosh et al, 2005). This suggested that an increased time interval would not result in any extra cleavage sites.…”
Section: Calpain-mediated Proteolysis Of P19 and Calpastatin Inhibitomentioning
confidence: 52%
“…Early studies suggested that calpains preferentially cleave peptide bonds with a Leu or a Val residue in the P2 position. More complete data, however, indicated that substrate specificity of the calpains is controlled by the conformation of a polypeptide chain and not by an amino acid sequence (Harris et al, 1988;Stabach et al, 1997;Ghosh et al, 2005). In general, the literature data indicate that the calpains cleave target proteins at a limited number of sites and produce large polypeptide fragments rather than small peptides or amino acids (Sasaki et al, 1984;Croall and Demartino, 1991;Goll et al, 2003).…”
Section: Discussionmentioning
confidence: 99%